Parathyroidectomy improves cardiovascular risk factors in normocalcemic and hypercalcemic primary hyperparathyroidism - Beysel, Selvihan (BMC Cardiovasc Disord, 2019)
BACKGROUND: Parathyroidectomy has ameliorated cardiovascular risk factors in patients with hypercalcemic primary hyperparathyroidism (PHPT), but the effect of parathyroidectomy on normocalcemic PHPT is not exactly known. This case-controlled study aimed to investigate the effect of parathyroidectomy on cardiovascular risk factors in patients with normocalcemic and hypercalcemic PHPT. METHODS: Subjects with normocalcemic PHPT (n = 35), age- and sex-matched hypercalcemic PHPT (n = 60) and age- and sex-matched control (n = 60) were included. Cardiometabolic disorders were investigated with traditional cardiometabolic risk factors and the Framingham cardiovascular risk score (CRS) before and 6 months after parathyroidectomy. RESULTS: Diabetes, dyslipidemia, hypertension, obesity, insulin resistance, osteoporosis, having fractures were similarly increased in the hypercalcemic and normocalcemic PHPT groups (p > 0.05) compared with the controls (p < 0.05). Blood pressures, glucose metabolism (glucose, insulin, HOMA-IR) and lipid profiles were similarly increased in the PHPT groups (p > 0.05) compared with the controls (p < 0.05). After parathyroidectomy, blood pressures, serum total cholesterol, and HOMA-IR were decreased in both PHPT groups (p < 0.05). CRS was lower in the controls (5.74 ± 3.24, p < 0.05). After parathyroidectomy, CRS was decreased in the normocalcemic (11.98 ± 10.11 vs. 7.37 ± 4.48) and hypercalcemic (14.62 ± 11.06 vs. 8.05 ± 7.72) PHPT groups. Increased blood pressures were independent predictors of serum iPTH. CONCLUSION: The normocalcemic and hypercalcemic PHPT groups had similarly increased cardiovascular risk factors, even independently of serum calcium. Parathyroidectomy ameliorated the increased cardiovascular risk factors in both normocalcemic and hypercalcemic PHPT.